2020
DOI: 10.1371/journal.pone.0229602
|View full text |Cite
|
Sign up to set email alerts
|

Human extracellular vesicles and correlation with two clinical forms of toxoplasmosis

Abstract: AimThis study analyzed microvesicles and exosomes, called as extracellular vesicles (EVs) excreted in serum and cerebrospinal fluid (CSF) from patients with cerebral or gestational toxoplasmosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 64 publications
(87 reference statements)
3
27
0
Order By: Relevance
“…The interaction between both organisms causes the stimulation of host EVs and protective immune response against T gondii derived EVs. These findings were well‐described before 24,36,44 . In addition, T gondii derived EVs used as immunogen caused an immune response capable of reducing the levels of tachyzoites in mouse blood, contributing to parasitaemia reduction and survival indexes increase 27,29,30 …”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The interaction between both organisms causes the stimulation of host EVs and protective immune response against T gondii derived EVs. These findings were well‐described before 24,36,44 . In addition, T gondii derived EVs used as immunogen caused an immune response capable of reducing the levels of tachyzoites in mouse blood, contributing to parasitaemia reduction and survival indexes increase 27,29,30 …”
Section: Discussionsupporting
confidence: 59%
“…These studies, also, proved that EVs carry pro‐inflammatory factors, including miRNAs, which directly cause the activation of cytokine production 31‐35 . In a previous study, we have shown a significant increase of EVs released in sera of patients with toxoplasmosis (with positive PCR for T gondii ), when they were compared with EV concentration released in sera of healthy individuals 36 . Consequently, high production of EVs could be correlated with the imbalance in immune response.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…EV production by some host cells types increases in infectious disease [ 86 , 87 ], and viruses, fungi, bacteria, and parasites have all been shown to directly stimulate host EV production [ 50 , 54 , 55 , 88 ]. A quantitative increase in host EV release has been demonstrated following an extracellular challenge of alveolar epithelial cells with heat-sacrificed bacteria, finding that the elicitor of such response was bacterial CpG DNA binding to endosomal TLR9 receptors [ 85 ].…”
Section: Host Ev-mediated Response To Infectionmentioning
confidence: 99%
“…TEM and NTA analysis identified vesicles with circular or elliptical vesicular structures ranging from 50 to 200 nm in diameter, the shape and size of which were similar to those described in our previous study and to those released by other helminths [ 14 ], such as Taenia asiatica , Echinococcus granulosus , and Echinococcus multilocularis [ 12 , 20 , 25 ]. The transmembrane proteins CD9 and CD63 are considered as exosomal markers and are frequently used to identify exosomes after isolation [ 26 , 27 ]. Our ITEM analysis results showed that CD9 and CD63 were detected in exosome-like vesicles from T. pisiformis metacestodes.…”
Section: Discussionmentioning
confidence: 99%